Modelagem da qualidade das águas superficiais da bacia hidrográfica do açude Santa Cruz do Apodi-RN - Silva, Wagner Bandeira da (Universidade Federal Rural do Semi-Árido, 2018)
The Santa Cruz do Apodi Watershed (SCAW) presents serious problems of aggression to the environment in almost all its extension at the present time, either by pollution or contamination, rendering unviable the multiple uses of the waters in certain areas, altering the capacity of recovery of the water resources. In this context, the present work aims to perform the modeling of the surface water quality of the Santa Cruz do Apodi-RN hydrographic basin, from 2008 to 2016, in order to generate subsidies for the management of the natural resources of the basin, providing a basis of products that will help in the planning and integrated management of the elements of its environment, with focus on the maintenance of its water resources in function of multiple uses. In this perspective, through the collection of secondary data from the Blue Water reports, univariate and multivariate statistical techniques were used for linear correlation analysis, Principal Components Analysis (PCA), as well as geostatistics. The linear correlation made it possible to identify the dependence between physical, chemical and biological variables. The ACP synthesized the information contained in the set of original variables. During the dry period, the variables: total solids (STD), total phosphorus (FT), chlorophyll a (CRF) and salinity (SAL) stood out the others. While in the rainy season, a major component composed of STD and CRF was observed, with the other components related to randomness, possibly influenced by rainfall. The geostatistical analysis, through the calculation of the adjusted experimental semivariograms, explained the spatial variability of surface water quality in BHASCA. The range of homogeneous areas ranged from 820 to 43,080 meters. From this perspective, it was observed that the reservoirs of BHASCA are susceptible to eutrophication processes, due to the predominance of chemical and biological factors, either by the release of domestic effluents not treated by the municipalities that compose the basin or by the practice of activities agropastoris, which may be compromising and / or limiting the multiple uses of the waters in said basin, such as affecting the maintenance of biodiversity.
Artigo Acadêmico
Keywords: Gestão de recursos hídricos; Estatística multivariada; Geoestatística; ENGENHARIAS::ENGENHARIA SANITARIA